Improving Speaking Ability through the Use of Advertisement for Management Students - Paskalina Widiastuti Ratnaningsih (The Future of Education Journal, 2026)
This study aims to discover speaking ability through advertisement in English. Speaking is one of English skills needed in working area. By having fluent English, people can have chance globally. Students need to prepare to have good English when they are still in the university. Mangement students need to have good English in Business English for working after they graduate. Advertisement is as one of the topics in Business English that is used to improve speaking ability in English. The students advertise products in English. This research used survey research. It used closed-ended questionnaire and open ended questionnaire. The results were students’ English speaking ability improved after advertising products in English. They were also more confident and had more vocabularies and knew how to make good sentences. Future studies can focus on exploring other topics of English in other study programs and compare the results of the improvement in speaking English.